2017
DOI: 10.5296/jebi.v4i1.10566
|View full text |Cite
|
Sign up to set email alerts
|

Microfinance and Performance of Micro and Small Enterprises: Does Training have an Impact

Abstract: 2 indicators of MSEs who owners have been given training against those whose owners have never been given any kind of training. In order to conduct study survey research has been conducted and a sample of 384 MSEs was selected on simple random basis. The findings revealed that all the performance indicators including sales increase, income increase, assets increase, employment increase, and meeting household expenses have shown a significant difference among the two groups. The findings of the study are very i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…Given that training is one of the important microfinance programmes, Kessy and Temu (2010) found that firms that were managed by owners with business training expected an increase in assets and sales as compared to those who did not. Haider, Asad, Fatima, and Zain Ul Abidin (2017) supported this earlier finding. Interestingly, Al Mamun (2014) found that group-based microcredit programme participation strengthened formal social bonding which led to an increase in productive assets.…”
Section: Literature Reviewsupporting
confidence: 86%
See 1 more Smart Citation
“…Given that training is one of the important microfinance programmes, Kessy and Temu (2010) found that firms that were managed by owners with business training expected an increase in assets and sales as compared to those who did not. Haider, Asad, Fatima, and Zain Ul Abidin (2017) supported this earlier finding. Interestingly, Al Mamun (2014) found that group-based microcredit programme participation strengthened formal social bonding which led to an increase in productive assets.…”
Section: Literature Reviewsupporting
confidence: 86%
“…This finding also extended the MFI initial goal in terms of poverty alleviation through women empowerment. Many studies have shown consistent findings of the advantages of microfinance programs (Ferdousi, 2015; Haider, Asad, Fatima, & Abidin, 2017; Mahmood & Mohd Rosli, 2013; Mamun, 2016). These have proven that microfinance programmes had a positive impact on microenterprise performance.…”
Section: Literature Reviewmentioning
confidence: 74%
“…SMEs have been accepted as the engine of economic growth and the promoter of equitable development (Christopher, 2007). The activities of SMEs to a reasonable level create employment, which helps the government generate a lot of revenue through taxes used for the developmental project (Haider, Asad, Fatima & Abidin, 2017). Government generates a lot of revenue through taxes paid by small businesses which are used to undertake development projects in the country (Abor & Quartey, 2010).…”
Section: Roles Small Business Play In Developing Countriesmentioning
confidence: 99%
“…For instance, in Ghana, 92 percent of businesses are small businesses, and they contribute 70 percent to GDP and 80 percent to employment. The activities of small businesses to a larger extent creates job (Agwu & Emeti, 2014;Boadu, Gabriel, Appiah & Dwomo-Fokuo, 2014;Haider, Asad, Fatima & Abidin, 2017), and government generate a lot of revenue through taxes paid by small businesses which are used to undertake developmental projects in the country (Abor & Quartey, 2010). Due to the significant role small businesses play, the growth and sustainability of them is crucial for economic stability and development.…”
Section: Introductionmentioning
confidence: 99%